Mirage in the West : A History of the French Image of American Society to 1815 - Echeverria, Durand (Book collections on Project MUSE., 1957)
" ... A gracefully written, brief, but remarkably complete account of the varieties and vicissitudes of French opinion regarding the English colonies and, to 1815, the U.S ... a major contribution."--William and Mary QuarterlyOriginally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905